High-efficiency broadband achromatic metalens for near-IR biological imaging window - Wang, Yujie; Chen, Qinmiao; Yang, Wenhong; Ji, Ziheng; Jin, Limin; Ma, Xing; Song, Qinghai; Boltasseva, Alexandra; Han, Jiecai; Shalaev, Vladimir M.; Xiao, Shumin (Nature communications, 2021)
Over the past years, broadband achromatic metalenses have been intensively studied due to their great potential for applications in consumer and industry products. Even though significant progress has been made, the efficiency of technologically relevant silicon metalenses is limited by the intrinsic material loss above the bandgap. In turn, the recently proposed achromatic metalens utilizing transparent, high-index materials such as titanium dioxide has been restricted by the small thickness and showed relatively low focusing efficiency at longer wavelengths. Consequently, metalens-based optical imaging in the biological transparency window has so far been severely limited. Herein, we experimentally demonstrate a polarization-insensitive, broadband titanium dioxide achromatic metalens for applications in the near-infrared biological imaging. A large-scale fabrication technology has been developed to produce titanium dioxide nanopillars with record-high aspect ratios featuring pillar heights of 1.5 µm and ~90° vertical sidewalls. The demonstrated metalens exhibits dramatically increased group delay range, and the spectral range of achromatism is substantially extended to the wavelength range of 650–1000 nm with an average efficiency of 77.1%–88.5% and a numerical aperture of 0.24–0.1. This research paves a solid step towards practical applications of flat photonics. Though broadband achromatic metalens are attractive for biological applications, existing metalenses show limited performance in the biological imaging window. Here, the authors report high-efficiency broadband achromatic metalens featuring record-high aspect ratio titanium dioxide metasurfaces.